ECONOMETRIC DETERMINATION OF VOTING BEHAVIOUR - NICOLAE-MARIUS JULA; NICOLETA JULA (Challenges of the Knowledge Society)
In this paper, we are testing the responsive hypothesis: if the economy is growing strongly and unemployment is low, the incumbent party has a very good chance of retaining office. When the economy is faltering, voters will more likely vote for change. We use econometric models for forecasting, based on economic data, the voter's choices and the evolution of the economy under the influence of political pressure.